The effects of preoperative glenohumeral osteoarthritis on rotator cuff repair: A systematic review and meta-analysis. - Sen Fang; Junwen Liang; Xudong Yang; Cairang Daoji; Zhixuan Nian; Mingchun Li; Jin Jiang; Xiangdong Yun (PLoS ONE, 2025)
Purpose This meta-analysis was carried out to evaluate the clinical effectiveness of rotator cuff repair surgery in treating rotator cuff tears in individuals with mild glenohumeral osteoarthritis (GHOA). Methods A computer-based search was conducted across multiple databases including PubMed, Embase, Web of Science, and Cochrane Library using the keywords "Shoulder Joints", "Osteoarthrosis", and "rotator cuff". Only studies focusing on patients with GHOA who underwent rotator cuff repair were considered for inclusion. The pertinent data was extracted and assessed for heterogeneity. Results A total of 5 studies involving 924 patients were included in the meta-analysis. The treatment outcomes of patients with rotator cuff tears accompanied by mild GHOA and those with simple rotator cuff tears after rotator cuff repair were comparable in terms of retear(OR: 1.24; 95% CI 0.82-1.89; P = 0.31). The postoperative functional scores: the VAS score (MD: 0.14; 95% CI -0.19-0.47; P = 0.41)、ASES score (MD: -0.33; 95% CI -1.64-0.99)were similar between the two groups. Subgroup analysis of rotator cuff tears(small to moderate, MD: 0.85; 95%CI -0.65-2.39; p = 0.28; large to massive, MD: -1.94; 95% CI -8.45-4.58; P = 0.56), showed no difference in postoperative ASES scores between the two groups. Constant score (MD:-3.20; 95% CI -6.33-0.08; P = 0.04), external rotation (ER) in Range of motion (ROM) (MD: -4.42; 95% CI -6.72-2.13; P = 0.0002) and forward flexion (FF) in ROM(MD: -4.22; 95% CI -8.28-0.15; P = 0.04) were superior in patients with simple rotator cuff tears compared to those with rotator cuff tears accompanied by GHOA. Conclusion Patients with rotator cuff tears and mild GHOA can achieve shoulder joint restoration after shoulder cuff repair surgery, and there is only a certain difference in postoperative Constant Score and ROM between these two groups. Trial registration PROSPERO registration CRD42024565212.